DNA methylation in cell differentiation and reprogramming: an emerging systematic view. (July 2010) - Huang, Kevin; Fan, Guoping
Embryonic stem cells have the unique ability to indefinitely self-renew and differentiate into any cell type found in the adult body. Differentiated cells can, in turn, be reprogrammed to embryonic stem-like induced pluripotent stem cells, providing exciting opportunities for achieving patient-specific stem cell therapy while circumventing immunological obstacles and ethical controversies. Since both differentiation and reprogramming are governed by major changes in the epigenome, current directions in the field aim to uncover the epigenetic signals that give pluripotent cells their unique properties. DNA methylation is one of the major epigenetic factors that regulates gene expression in mammals and is essential for establishing cellular identity. Recent analyses of pluripotent and somatic cell methylomes have provided important insights into the extensive role of DNA methylation during cell-fate commitment and reprogramming. In this article, the recent progress of differentiation and reprogramming research illuminated by high-throughput studies is discussed in the context of DNA methylation.